The Choice Problems Of Presidential System In Indonesia Post-Reformation - Siti Rodhiyah Dwi Istinah; Aryani Witasari; Fajar Fathan Fuadi; Muhammad Ali Maskun (Jurnal Daulat Hukum, 2021)
The purpose of this paper is to find out and analyze the problems of the choice of the presidential system in the post-reformation of Indonesian state administration. The research method used is normative juridical, using a statutory approach. The data used is secondary data, with primary legal material from the 1945 Constitution and other laws and regulations. The results show that the choice of a presidential government system becomes a problem when juxtaposed with the multi-party system (combined phrase of political parties) in the 1945 Constitution. The MPR in the trial between 1999 and 2002 did not choose a quasi-presidential system in the original 1945 Constitution as well as a parliamentary system and explicitly transplant the American-style presidential system of government, without paying attention to ideological reasons and the identity and traditions of the state that have been explored by the nation's founders such as Soepomo, Soekarno and Muhammad Hatta.